Carbonization 2.0: How to produce more charcoal with less wood and emissions - Schure, J.; Hubert, D.; Ducenne, H.; Kirimi, M.; Awono, A.; Mpuruta-Ka-Tito, R.; Mumbere, G.; Njenga, M. (CIFOR-ICRAF, 2021)
This publication is part of a series of briefs describing findings from the EU-funded Governing Multifunctional Landscapes Sustainable Woodfuel project, which aims to contribute to knowledge, options, and networks for more sustainable woodfuel value chains across Sub-Saharan Africa.